A retrospective review of changes and challenges in the use of antiseizure medicines in Dravet syndrome in Norway. Issue 3 (6th July 2020) - Heger, Katrine; Lund, Caroline; Larsen Burns, Margrete; Bjørnvold, Marit; Sætre, Erik; Johannessen, Svein I.; Johannessen Landmark, Cecilie
Abstract: Objective: Dravet syndrome is a developmental and epileptic encephalopathy characterized by severe and drug‐resistant seizures in early childhood, followed by developmental delay. The purpose of this study was to investigate aspects of pharmacological treatment of Norwegian patients with Dravet syndrome, focusing on the use of antiseizure medicines (ASMs) and identifying treatment challenges. Methods: Patients were identified through medical registries at the National Center for Epilepsy in Norway and National Center for Rare Epilepsy Related Disorders during 2008‐2018. Additional clinical data were obtained from medical records and laboratory request forms. Results: We identified 53 patients with Dravet syndrome, 30/23 males/females, aged 2‐50 years. The majority of patients with known seizure frequency experienced frequent seizures, 80% (n = 35/44). Only two patients were seizure‐free. Valproate (n = 48), clobazam (n = 45), levetiracetam (n = 30), and stiripentol (n = 38) were most commonly used, previous or current use. More than one‐third (n = 20) had tried sodium channel blockers (including lamotrigine), but these drugs were used less during the last decade. Polytherapy was common, 81% (n = 43) used two or more ASMs, and eight of these patients used 4‐5 drugs (15%). Several challenges were identified: high seizure frequency, comorbidities, treatment changes with a wide range of ASMs, common use of oral gastro‐tubes, extensive polypharmacy, and drug interactions. Significance: The use of ASMs has changed over the last decade, in accordance with updated international recommendations. Various treatment challenges were identified. This vulnerable group of patients needs close follow‐up for an optimal treatment outcome.